Inhibitory Activity of Natural Synergetic Antimicrobial Consortia Against Salmonella enterica on Broiler Chicken Carcasses - Zhang, Liya; Ben Said, Laila; Diarra, Moussa Sory; Fliss, Ismail (Frontiers in Microbiology, 2021)
The currently most utilized antimicrobial agent in poultry processing facilities is peracetic acid, a chemical increasingly recognized as hazardous to human health. We evaluated the efficacy of mixtures of natural antimicrobial compounds, namely reuterin, microcin J25 and lactic acid, for reducing the viability of Salmonella enterica and total aerobes on broiler chicken carcasses. The compounds were compared singly and in combination, to water and 0.1% peracetic acid. The minimum inhibitory concentrations of reuterin, lactic acid and microcin J25 against S. enterica serovar Enteritidis were respectively 2 mM, 0.31% and 0.03 μM. In vitro, the combinations reuterin + lactic acid and reuterin + microcin J25 were synergic, making these compounds effective at concentrations 4 times lower than that used alone. Salmonella viable counts fell to zero within 10 min of contact with reuterin + lactic acid at 10 times the concentrations used in combination, compared to 18 h in the case of reuterin + microcin J25. Sprayed onto chilled chicken carcasses, this reuterin + lactic acid mixture reduced Salmonella spp. counts by 2.02 Log CFU/g, whereas reuterin + microcin J25 and peracetic acid reduced them by respectively 0.83 and 1.13 Log CFU/g. The synergy of reuterin with lactic acid or microcin J25 as inhibitors of bacterial growth was significant. Applied as post-chill spray, these mixtures could contribute to food safety by decreasing Salmonella counts on chicken carcasses.